2023
DOI: 10.1111/joor.13427
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral behaviours in general dental patients attending a university clinic in Italy

Abstract: Background Oral behaviors represent a diverse array of habits beyond the physiological behaviors of the stomatognathic system. Objective To describe the prevalence of different oral behaviors, as reported with the Oral Behavior Checklist (OBC‐21), in a convenience sample of patients attending an Italian university clinic for routine dental cares. Methods In this study, charts of adult patients presenting to the dental department of a regional hospital in Trieste, Italy, from January 2018 and January 2019 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Similar results were also supported by multiple articles 44‐46 . By contrast, other studies have demonstrated a significant positive correlation between salivary cortisol levels in both the case and the CG 47‐51 . These discrepancies in the literature suggest that individual variations in stress thresholds may contribute to the diverse findings across studies 52‐54 …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar results were also supported by multiple articles 44‐46 . By contrast, other studies have demonstrated a significant positive correlation between salivary cortisol levels in both the case and the CG 47‐51 . These discrepancies in the literature suggest that individual variations in stress thresholds may contribute to the diverse findings across studies 52‐54 …”
Section: Discussionsupporting
confidence: 54%
“…4 4-46 By contrast, other studies have demonstrated a significant positive correlation between salivary cortisol levels in both the case and the CG. [47][48][49][50][51] These discrepancies in the literature suggest that individual variations in stress thresholds may contribute to the diverse findings across studies. [52][53][54] Regarding IL-1, Ce et al 32 reported significantly higher levels in patients with TMD alone compared to the CG, irrespective of fibromyalgia assessment.…”
Section: Discussionmentioning
confidence: 99%
“…71 Amongst those, the OBC has been selected for the STAB 24 and a modified version of the BRUX scale has been included in the BruxScreen. 25 The OBC is widely used to investigate the prevalence of various oral behaviours, 72,73 and it contains four questions referring to behaviours that may be part of the AB spectrum (i.e., teeth grinding, teeth clenching, teeth contact, mandible bracing). 71 The questions are formulated in the form of "How often do you do each of the following activities, based on the last month?".…”
Section: Non-instrumental Assessmentmentioning
confidence: 99%
“…1,16 According to a study conducted by Sambataro et al, elastics have an impact not only on the teeth but also on the TMJ position. [17][18][19][20][21][22][23][24][25] Moreover, a study conducted by Tanaka et al demonstrated that the elastic modulus of the TMJ disk exhibits an increase with age. 26 The mechanical loading that the TMJ structures experience depends significantly on the disk's stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence indicates that the utilisation of Class II and Class III elastics may have an impact on the TMJ; however, the degree of influence may differ 1,16 . According to a study conducted by Sambataro et al., elastics have an impact not only on the teeth but also on the TMJ position 17–25 . Moreover, a study conducted by Tanaka et al.…”
Section: Introductionmentioning
confidence: 99%